Peran dan Wewenang Dewan Perwakilan Rakyat Daerah (DPRD) dalam Pelaksanaan Fungsi Anggaran terhadap APBD Provinsi Sumatera Utara - Nurul Hafizah (VISA: Journal of Vision and Ideas, 2022)
This research discusses the duties and authorities of the Regional House of Representatives (DPRD) in implementing the Regional Revenue and Expenditure Budget (APBD) in North Sumatra Province, the obstacles experienced, and efforts to overcome these obstacles. This research uses a qualitative research method of problem research. Information obtained from the results of questions and answers and literature research. The results of the research prove that the DPRD of North Sumatra Province has a very significant use in calculations. Barriers that arise relate to budget constraints, time adaptation and the many different activities of DPRD members, as well as communication aspects. There have also been attempts to overcome obstacles in this regard, namely increasing the budget, adapting the duration and number of activities, and pressure from the Deliberative Body so that all DPRD members can appear in APBD reviews with administrators. Keywords: Budget function, DPRD North Sumatra, APBD